THE NARRATOR’S MOTIVES CONCERNING JULIANA’S LETTERS IN HENRY JAMES’S THE ASPERN PAPERS - Ahmad Ahmad (Elite : English and Literature Journal, 2020)
This study questions how the narrative voice of Henry James’s The Aspern Papers shapes the reader's understanding of the narrator’s motives concerning Juliana’s letters received from Jeffrey Aspern. This is qualitative analytical research in which ‘unreliable narrator’ theory was used to analyze and discuss the data from primary and secondary resources. This paper also links Booth’s idea to Schneider’s critics about unreliable narrator theory. Although The Aspern Papers’ narrator is unreliable due to his unpredictable and unstable actions, the researcher argues that The Aspern Papers’ narrator who also becomes the main character of the story wants to possess Juliana’s letters for his benefits. Should he get the letters, he would be able to “sell” Aspern’s life to the public, and thus he could get financial profit or personal profit for his career as a journalist, a writer, or a publisher.